NILAI KONSUMEN WISATA DALAM RUANG PROMOSI DIGITAL - Andry Rivan Sumara; Saepudin Saepudin; Yudha Asmara Dwi Aksa (Pusat Penelitian dan Pengembangan Aplikasi Informatika, Informasi dan Komunikasi Publik (APTIKA dan IKP) Badan Penelitian dan Pengembangan SDM Kementerian Komunikasi dan Informatika, 2019)
Abstract Consumer value is the basic fundamental of marketing communications. Promotional materials on media have to consider the value of consumer expectations, wishes, experiences, and perceptions. This means the product or service has to interact with consumers (need, expectation, experience, and perception). The emergence of new media becomes an alternative for marketers to promote goods or services to their target market. But the emergence of this new media in addition to being an opportunity also becomes a challenge in presenting the best consumer value. The purpose of this research is to find out the ways of creating the value of local tourism on social media. The researcher chooses the official account of Twitter of Government Tourism and Culture Office of West Java as an object of research. The focus of this research is promotional content on the official account of Twitter and consumer value creation. This research is content analysis. The purpose of this research is the identification of the value and effort of tourism, consumer value creation, especially on social media. The output of this research is patterns of consumer tourism, value-creation. Consumer value creation is not applied in visual and textual comprehensively. In addition, based on the content of this account, the local tourist is as the main target market. The values in this account are created for local tourists and not for international tourist. Keywords: consumer value, tourism, tourism marketing.